(untitled) (Biosaintifika: Journal of Biology & Biology Education, 2024)
Pacific Seabream, Acanthopagrus pacificus, is a popular marine fish from the Sparidae family. This species is an economically essential fisheries commodity in the south-coast Java, Indonesia. However, limited studies are available on A. pacificus in Indonesia. Only two studies reported the presence of A. pacificus in South-Coast Java. No study has been carried out on the biology of A. pacificus from south-coast Java. Therefore, biological studies of A. pacificus are needed, including genetic diversity studies. This study aimed to evaluate the genetic diversity of A. pacificus in South-Coast Java using the cytochrome c oxidase gene. Fish samples were bought from Bantul Fishing Harbor, Yogyakarta, Panganadaran Fishing Port, Bojongsalawe Fish Auction Center, West Java, and Binuangeun Fishing Harbor in Lebak Regency, Banten. The genetic marker was processed in PT. Genetika Science Indonesia follows the company procedure. Haplotype and nucleotide diversity were calculated mathematically using Arlequin software. The result showed that polymorphic loci were only 1.3%, indicating low polymorphisms. A. pacificus showed haplotype and nucleotide diversities of 0.511±0.110 and 0.15%±0.12%, respectively. Those values indicated low genetic diversity. This study concluded that the A. pacificus population in South-Coast Java showed low genetic diversity. This study provides the first data about the genetic diversity of A. pacificus in South-Coast Java, which is essential data for fisheries management.